Euroscepticism or nationalism — which better explains the decision of the British to leave the European Union? - Danel, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article is dedicated to the 2016 United Kingdom European Union Referendum (known as the Brexit Referendum) that took place on 23 June 2016 and resulted in the majority of the votes cast being in favor of leaving the EU. As a consequence, on 31 January 2020, the United Kingdom of Great Britain and Northern Ireland oﬃcially withdrew from the European Union.The purpose of this article is to try to make an interpretation of Brexit by attempting to answer a question of which of these two factors — Euroscepticism or nationalism — more heavily determined the will of the people and inﬂuenced the result of the referendum. Euroscepticism has accompanied the British from the very moment their country became part of the united Europe. The importance of nationalism in turn, analyzed as both English nationalism and British nationalism, has increased signiﬁcantly in recent years.Using the collected research material, the author will try to prove the thesis that, in fact, these two factors are inextricably linked and it is very diﬃcult to examine them separately. Euroscepticism, so deeply rooted in the British society, seems to have been — especially in recent years — the driving force of English and British nationalism.
Keywords: Brexit; Unia Europejska; Wielka Brytania; Eurosceptycyzm; angielski nacjonalizm; brytyjski nacjonalizm